Refugee Agency and Autonomy in English Language Acquisition - Carson, Lorna (My University, 2008)
This article looks at an ethnographic study conducted at Integrate Ireland Language and Training1, an organization which provides English language courses for adult refugees. The research project was a qualitative, longitudinal investigation which explored the motivational role of goal-setting in adult language learners. During a twelve-month period (2003-2004), multiple data-gathering techniques were employed including participant observation, group interviews with learners, teacher interviews, attitudinal questionnaires, and archival research. The research aimed to record and to analyze the motivational impact of a curriculum designed to encourage learner autonomy. In this paper, I give a brief overview of the context of refugees in Ireland and the provision of English language training. I explore the concept of autonomy in language learning, argue that it is particularly relevant in the context of language provision for refugees, and present the work of Integrate Ireland Language and Training. I then review the main characteristics of ethnographic research and data collection methods, before providing a narrative account of the experience of learning English as a refugee in Ireland, and the relevance of encouraging autonomy in the language classroom.
PUBLISHED
Keywords: Refugees, Autonomy; Ethnography; Second Language Learning